Abstract 227: Combined Technique Versus Stent‐Retriever Alone: Angioarchitectural and Technical Analysis - Mohamed A. Tarek; Pedro N. Martins; Mahmoud H. Mohammaden; Mateus Damiani Monteiro; Jonathan A. Grossberg; Jay C. Dolia; Aqueel Pabaney; Raul G. Nogueira; Diogo C. Haussen (Stroke: Vascular and Interventional Neurology)
Introduction Combined technique mechanical thrombectomy with contact aspiration with stent‐retriever has been shown to lead to comparable final reperfusion rates compared with stent retriever alone. We aimed to explore if anatomical and technical features could have interaction with the chances of reperfusion by each technique. Methods Retrospective analysis of a prospective mechanical thrombectomy (MT) database. Inclusion criteria: anterior circulation large vessel occlusion(LVO) due to carotid terminus or proximal MCA(M1) occlusion, first‐line stent‐retriever (SR) alone or combined technique (SR plus aspiration), and angiographic run with stent in place. The primary analysis was the interaction between clinical and angiographic characteristics and first‐line MT modality on first‐pass effect (FPE; first‐pass eTICI2c‐3). Secondary analyses aimed to evaluate predictors of FPE. Results A total of 150 patients were included in the analysis (SR alone,n=62 vs. combined technique, n=88). Demographics, vascular risk factors and NIHSS were comparable between groups. The SR group had higher IV‐tPA use (41.9%vs.26.1%,P=0.04), higher rates of FPE(64.5%vs.47.7%,P=0.04) but similar baseline ASPECTS, CTA collateral score, clot burden, as compared to the combined technique. Anatomical and technical variables (reperfusion channel, SR position in dominant MCA division, angle of interaction, diameter of stent proximal to clot, diameter of stent distal to clot, type of extracranial carotid or cavernous carotid tortuosity, clot length were comparable between both groups. None of the anatomical and technical factors were found to have an interaction with the modality (SR alone vs combined technique) on the chances of FPE (Pinteraction >0.05)(Figure). FPE was observed in 54.6% of the entire cohort. Multivariable analysis showed that use of IV‐tPA(OR 156.5,95%CI 4.59‐5334.8,P=0.005), lower angle of interaction (OR 0.94,95%CI 0.89‐0.99,P=0.03), presence of reperfusion channel (OR 145.8,95%CI 1.96‐108277.4),P=0.02), higher clot burden score (OR 8.17,95%CI 1.38 ‐48.21,P=0.02), type‐3 cavernous ICA tortuosity (OR 0.001,95%CI 0‐0.23,P=0.01) were independently associated FPE. Conclusion We could not identify any anatomical or technical features that predisposed to a benefit in adding catheter aspiration to SR thrombectomy. IV r‐TPA, clot burden score, presence of reperfusion channel, type of cavernous carotid tortuosity, and angle of interaction were found independently associated with FPE. Large sample studies are warranted.